A lexical decision task for rapid estimation of crystalized vocabulary knowledge in Thai - Graham Pluck; Alexis Sirisomboonwong; Smriti Sitani; Carl Piaf; Suphasiree Chantavarin (PLoS ONE, 2026)
A useful distinction within cognitive and brain sciences is that between fluid and crystallized ability. Although fluid ability is widely studied, crystalized ability, which draws on acquired, declarative semantic knowledge and the mental lexicon, has been less well studied. Partly this is due to the culture and language specificity of assessment methods. We developed and assessed the psychometric properties of a simple 42-item lexical decision task that could be used with Thai speakers to assess the breadth of their crystalized vocabulary knowledge. A large sample of responses from 662 Thai-speaking participants, collected online, was used to refine the scale through exploratory factor analysis, and establish its internal consistency. A smaller sample of 90 participants was interviewed to establish validity of the task as a measure of Thai vocabulary. Large positive correlations (i.e., > .3) were found between the Thai Lexical Decision Task and measures of verbal fluency, particularly in the first 30 seconds of responding, and with other measures of Thai language skill. Temporal stability of the scale was assessed in a subsample of 27 participants. This confirmed that the Thai Lexical Decision Task has little obvious practice effect and excellent test-retest reliability. We also observed the expected positive associations with age, educational level, and self-reported proficiency in the language, supporting the ability of the task to measure acquired, crystalized knowledge. This new task could be used to estimate cognitive ability in Thai adults and shows potential as a measure of premorbid cognitive function for use in neuropsychological assessments.